Rituximab and Abatacept Are Effective in Differential Treatment of Interstitial Lymphocytic Lung Disease in Children With Primary Immunodeficiencies - Rodina, Yulia; Deripapa, E.; Shvets, O.; Mukhina, A.; Roppelt, A.; Yuhacheva, D.; Laberko, A.; Burlakov, V.; Abramov, D.; Tereshchenko, G.; Novichkova, G.; Shcherbina, Anna (Frontiers in Immunology, 2021)
Background: Interstitial lymphocytic lung disease (ILLD), a recently recognized complication of primary immunodeficiencies (PID), is caused by immune dysregulation, abnormal bronchus-associated lymphoid tissue (BALT) hyperplasia, with subsequent progressive loss of pulmonary function. Various modes of standard immunosuppressive therapy for ILLD have been shown as only partially effective. Objectives: To retrospectively evaluate the safety and efficacy of abatacept or rituximab in treatment of ILLD in children with PID. Methods: 29 children (median age 11 years) with various forms of PID one of the two therapy regimens predominantly based on the lesions’ immunohistopathology: children with prevalent B-cell lung infiltration received rituximab (n = 16), and those with predominantly T-cell infiltration received abatacept (n = 17). Clinical and radiological symptoms were assessed using a severity scale developed for the study. Results: The targeted therapy with abatacept (A) or rituximab (R) enabled long-term control of clinical (A 3.4 ± 1.3 vs. 0.6 ± 0.1; R 2.8 ± 1 vs. 0.7 ± 0.05, p < 0.01) and radiological (A 18.4 ± 3.1 vs. 6.0 ± 2.0; R 30 ± 7.1 vs. 10 ± 1.7, p < 0.01) symptoms of ILLD in both groups and significantly improved patients’ quality of life, as measured by the total scale (TS) score of 57 ± 2.1 in treatment recipients vs. 31.2 ± 1.9 before therapy (р < 0.01). Conclusions: ILLD histopathology should be considered when selecting treatment. Abatacept and rituximab are effective and safe in differential treatment of ILLD in children.